The Effect of Patients’ Psychological Contract with Pharmacists on Medication Adherence: A Qualitative Study - Gu Y; Mu X; Zhang Y; Tang Y; Zhang T; Tang F (Patient Preference and Adherence, 2023)
Yang Gu,1– 4,* Xingrui Mu,1,3,4,* Yan Zhang,1,3,4 Yunyan Tang,4,5 Ting Zhang,4,6 Fushan Tang1,3,4 1Department of Clinical Pharmacy, Key Laboratory of Basic Pharmacology of Guizhou Province and School of Pharmacy, Zunyi Medical University, Zunyi, 563006, People’s Republic of China; 2Department of Pharmacy, People’s Hospital in Hezhang County, Bijie, 553200, People’s Republic of China; 3Key Laboratory of Basic Pharmacology of Ministry of Education and Joint International Research Laboratory of Ethnomedicine of Ministry of Education, Zunyi Medical University, Zunyi, 563006, People’s Republic of China; 4The Key Laboratory of Clinical Pharmacy of Zunyi City, Zunyi Medical University, Zunyi, 563006, People’s Republic of China; 5Department of Pharmacy, Affiliated Meitan People’s Hospital of Zunyi Medical University, Zunyi, 564100, People’s Republic of China; 6Department of Pharmacy, Guiyang Hospital of Stomatology, Guiyang, 550002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fushan Tang, Department of Clinical Pharmacy, Key Laboratory of Basic Pharmacology of Guizhou Province and School of Pharmacy, Zunyi Medical University, Zunyi, Guizhou, People’s Republic of China, Tel +86851 28642337, Fax +86851 28642334, Email fstang@zmu.edu.cn; fstang@vip.163.comObjective: To investigate the effect of psychological contract of outpatients with hospital pharmacists on medication adherence, providing reference for improving the management of patients’ medication adherence from the perspective of pharmacist-patient relationship and psychological contract.Methods: The 8 patients who received medication dispensing service at the outpatient pharmacies at the First Affiliated Hospital of Zunyi Medical University and the Second Affiliated Hospital of Zunyi Medical University were selected for face-to-face in-depth interviews through a purposive sampling method. In order to get more potential information and adjust flexibly according to the actual situation of the interview, the interviews were set as semi-structured, and the interview content was analyzed by using Colaizzi’s seven-step method of phenomenological analysis and NVivo11.0 software.Results: The following four themes about effects of patients’ psychological contract with hospital pharmacists on medication adherence were extracted: from the perspective of patients, the relationship between pharmacists and patients is generally harmonious; pharmacists can basically fulfil their responsibilities; patients’ medication adherence needs to be improved; the status of patients’ psychological contract with hospital pharmacists may affect medication adherence.Conclusion: The psychological contract of outpatients with hospital pharmacists has a positive effect on their medication adherence. Effective management on medication adherence should involve the management on patients’ psychological contract with hospital pharmacists.Keywords: psychological contract, medication adherence, pharmaceutical care, qualitative study